Step 1: Integrating \( \frac{\partial \phi}{\partial x} = 2xy^2 \).
\[
\phi = \int 2xy^2 dx = x^2 y^2 + f(y,z).
\]
Step 2: Integrating \( \frac{\partial \phi}{\partial y} = x^2z^2 \).
\[
\frac{\partial}{\partial y} (x^2 y^2 + f(y,z)) = x^2 z^2.
\]
Solving, we find:
\[
f(y,z) = y^2 z^2 + g(z).
\]
Step 3: Integrating \( \frac{\partial \phi}{\partial z} = 3x^2 y^2 z^2 \).
\[
\frac{\partial}{\partial z} (x^2 y^2 + y^2 z^2 + g(z)) = 3x^2 y^2 z^2.
\]
Solving, we find:
\[
\phi = x^3 y^2 z^2 + c.
\]
Step 4: Selecting the correct option.
Since \( \phi = x^3 y^2 z^2 + c \) matches, the correct answer is (B).